Effect of process parameters on enhanced biohydrogen production from tequila vinasse via the lactate-acetate pathway. (February 2019) - García-Depraect, Octavio; Rene, Eldon R.; Diaz-Cruces, Víctor F.; León-Becerril, Elizabeth
Graphical abstract: Highlights: BioH2 production from tequila vinasse via lactate-acetate pathway was studied. The influence of process parameters on bioH2 production was ascertained. BioH2 production depends on inoculum > substrate load > nutrients > solids content. BioH2 production: 124 NmL/g VSin and 225 NmL/L-h were achieved in this study. Abstract: In this study, a lactate-type fermentation entailing the consumption of lactate and acetate (lactate-acetate pathway) is proposed to deal with lactic acid bacteria (LAB) inhibition during the production of biohydrogen (bioH2 ) from tequila vinasse. The effects of total solids content, substrate concentration, nutrient formulation and inoculum addition on bioH2 production performance were investigated. Batch experiments were performed in a 3-L completely mixed reactor at 35 °C and pH 6.5–5.8. The lactate-acetate pathway mediated consistent bioH2 production which was influenced by inoculum addition followed by substrate concentration, nutrient formulation and solids content. Maximum bioH2 production rate (225 NmL/L-h) and yield (124 NmL/g VSadded ) were achieved by removing suspended solids and enhancing nutrient content, respectively. Illumina sequencing-based analysis revealed a dominance of Clostridium in the inoculum, which together with LAB and acetic acid bacteria shaped a keystone cluster for avoiding LAB inhibition while ensuring consistent bioH2 production performance.